The Study on the Possibility of Virtual Reality Museum Replacement in Reality Museum - Yu, YoungJe; Hyung June, Woo; Kim, Sun-Jeong; Geun Song, Chang (International Journal of Engineering and Technology, 2019)
In a great number of museums, there are curators in place to deliver information to the audience adjusting to the level of description depending on their age and/or level of intelligence. However, the reality is that there is not enough number of curator staffs. Due to such problem, it is practically impossible for every audience to be served by a curator. That is why audio guides and/or Near-Field Communication (NFC) tag systems have also taken place in museums.Â In this study, the proponents have implemented a â€œVirtual Reality museum (VR museum)â€ by utilizing the virtual reality technology that has already been used widely in the fields of film, education, etc., nowadays. A virtual reality museum had been created similar to the Hallym University museum. The museum was created with the use of 3D MAX and Unity 3D.Â  An NFC system has also been developed to describe the artifacts to the audience. The app has been implemented on mobile device such as tablet PC, or smartphone. A comparison was made with the real museum with curators, the real museum with NFC system and the VR Museum. There were 75 participants during the study. The research was carried out in the following order: First, an objective evaluation of the effect of the museum viewing was conducted on the visitors. Second, a subjective evaluation was also conducted about the overall feelings of the visitors on the museum viewing. Third, a comparative evaluation was performed on the usability among curator-assisted museum viewing, and museum viewing with NFC applications that provide help for the visitors of museums, and the virtual reality museum. Based on the three types of evaluation aforementioned, the study suggests that the curatorâ€™s function can be replaced by NFC app or virtual museum. In the aspect of providing useful information about exhibits, there is no difference among three methods of curator, NFC and VR.Â